Stability Analysis of Fractional Order Oscillating Systems - Kaliraj, K.; Priya, S. Mohana; Priya, P. K. Lakshmi; Vivik, J. Veninstine (Discontinuity, Nonlinearity, and Complexity, 2026)
The work resolves around the analysis of Ulam-Hyers stability and Ulam-Hyers-Rassias stability of Conformable fractional order control system. Initially, we utilize the concept of trigonometric functions such as sine and cosine to define the Conformable matrix to deduce the sufficient conditions for the system to admit stability. The theoretical study is authenticated by providing appropriate numerical simulation.